NFTs and Intellectual Property: Addressing Legal Certainty for Consumer Protection - Alif Ardiansyah; Nuzulia Kumala Sari (Rechtenstudent, 2024)
This paper aims to provide a view regarding NFT transactions in the future to provide legal certainty, especially for IPR by using normative research methods along with supporting theories to find that in fact NFT transactions in Indonesia are far from legal because they do not meet the rules of NFT transactions where PTSE regulations, especially NFT transactions, do not provide legal guarantees to their owners, one of which is the chain of suppliers, namely Opensea, which is not yet optimal, so there is a need for regulations or crypto exchanges, especially NFTs, which not only provide certainty but the crypto market in Indonesia does not experience scams because in terms of analysis NFTs can be categorized as inherity distinctives or as signs that inherently have distinguishing power, immediately if they get protection through use, because some parties often cheat by taking screenshots, but for parties who make legitimate transactions, they have a differentiating way of gaining access to increasing the digitalization of works has reduced the potential value of copyright scarcity, which has become a significant problem in copyright disputes.